2020
DOI: 10.1167/iovs.61.4.44
|View full text |Cite
|
Sign up to set email alerts
|

Monocular Deprivation Affects Visual Cortex Plasticity Through cPKCγ-Modulated GluR1 Phosphorylation in Mice

Abstract: Purpose To determine how visual cortex plasticity changes after monocular deprivation (MD) in mice and whether conventional protein kinase C gamma (cPKCγ) plays a role in visual cortex plasticity. Methods cPKCγ membrane translocation levels were quantified by using immunoblotting to explore the effects of MD on cPKCγ activation. Electrophysiology was used to record field excitatory postsynaptic potential (fEPSP) amplitude with the goal of observing changes in visual cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Western blot analysis was performed as previously described (Liu, Han, et al, 2019; Zhang et al, 2020; Zheng et al, 2021). Corpus callosum and the internal capsule from brain tissue or cells in six‐well plates rinsed three times with PBS were homogenized in Buffer C (50 mM Tris‐HCl, pH 7.5, 2 mM EDTA, 2 mM EGTA, 50 nM okadaic acid, 5 mM sodium pyrophosphate, 100 μM sodium vanadate, 1 mM DTT, 50 mM KF, 2% sodium dodecyl sulfate [SDS] and a protease inhibitor mixture) and sonicated.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as previously described (Liu, Han, et al, 2019; Zhang et al, 2020; Zheng et al, 2021). Corpus callosum and the internal capsule from brain tissue or cells in six‐well plates rinsed three times with PBS were homogenized in Buffer C (50 mM Tris‐HCl, pH 7.5, 2 mM EDTA, 2 mM EGTA, 50 nM okadaic acid, 5 mM sodium pyrophosphate, 100 μM sodium vanadate, 1 mM DTT, 50 mM KF, 2% sodium dodecyl sulfate [SDS] and a protease inhibitor mixture) and sonicated.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, WF-OCTA demonstrated more pronounced vascular involvement in the DCP, irrespective of the stage of DR. A recent study of 104 eyes with PDR showed a disproportion of lamellar capillary nonperfusion between the SCP and the DCP, the latter being more greatly involved in all the assessed quadrants [ 48 ]. The difference in the perfusion pressure between the SCP and the DCP could be a plausible explanation of this discrepancy [ 49 ].…”
Section: Wf-octa and Nonperfusion Areas In Drmentioning
confidence: 99%